Respuesta :
Answer:
multiply a term by 2 and add 1 to get the next term
Step-by-step explanation:
3×2=6 +1 =7
7×2=14+1= 15
15×2=30+1=31
Answer:
Multiply a term by 2 and add 1 to get the next term
Step-by-step explanation:
The first differences of terms are ...
7 -3 = 4
15 -7 = 8
31 -15 = 16
We notice that these increase by a factor of 2. This signifies an exponential sequence. That factor (2) will be the value that each term is multiplied by to get the next. This eliminates the choices "add 4" and "multiply a term by 3 ...".
Trying the remaining two choices, we find that the one that fits is the one shown above.
3+7 ≠ 15, so "the sum of the two preceding terms" doesn't work
2(3) +1 = 7; 2(7) +1 = 15; 2(15) +1 = 31, so "multiply by 2 and add 1" works fine